Right atrial pressure during exercise predicts survival in patients with pulmonary hypertension - Lichtblau, Mona; Bader, Patrick R.; Saxer, Stéphanie; Berlier, Charlotte; Schwarz, Esther I.; Hasler, Elisabeth D.; Furian, Michael; Grünig, Ekkehard; Bloch, Konrad E.; Ulrich, Silvia (Journal of the American Heart Association, 2020)
Background We investigated changes in right atrial pressure (RAP) during exercise and their prognostic significance in patients assessed for pulmonary hypertension (PH). Methods and Results Consecutive right heart catheterization data, including RAP recorded during supine, stepwise cycle exercise in 270 patients evaluated for PH, were analyzed retrospectively and compared among groups of patients with PH (mean pulmonary artery pressure [mPAP] ≥25 mm Hg), exercise‐induced PH (exPH; resting mPAP <25 mm Hg, exercise mPAP >30 mm Hg, and mPAP/cardiac output >3 Wood Units (WU)), and without PH (noPH). We investigated RAP changes during exercise and survival over a median (quartiles) observation period of 3.7 (2.8-5.6) years. In 152 patients with PH, 58 with exPH, and 60 with noPH, median (quartiles) resting RAP was 8 (6-11), 6 (4-8), and 6 (4-8) mm Hg (P<0.005 for noPH and exPH versus PH). Corresponding peak changes (95% CI) in RAP during exercise were 5 (4-6), 3 (2-4), and −1 (−2 to 0) mm Hg (noPH versus PH P<0.001, noPH versus exPH P=0.027). RAP increase during exercise correlated with mPAP/cardiac output increase (r=0.528, P<0.001). The risk of death or lung transplantation was higher in patients with exercise‐induced RAP increase (hazard ratio, 4.24; 95% CI, 1.69-10.64; P=0.002) compared with patients with unaltered or decreasing RAP during exercise. Conclusions In patients evaluated for PH, RAP during exercise should not be assumed as constant. RAP increase during exercise, as observed in exPH and PH, reflects hemodynamic impairment and poor prognosis. Therefore, our data suggest that changes in RAP during exercise right heart catheterization are clinically important indexes of the cardiovascular function.
Gesehen am 13.01.2020